ADVERTISING MANAGEMENT AS A BASIS FOR THE FORMATION OF EFFECTIVE MARKET ACTIVITY OF COMPANIES - USTIK, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article focuses on the study of the theoretical and methodological content of advertising management, outlines the main components of analytical research, taking into account modern digital transformations and digital adaptation of business to advertising, and elaborates on the directions of advertising policy implementation and tools for its effective implementation. The importance of advertising research is proved and the results of advertising management functioning in recent years and the dynamics of changes by country are presented. The basic factors of influence of advertising campaigns on the activities of business entities are outlined, and the influence of factors on the possibility of choosing models of marketing research in terms of advertising efficiency is formed. The key issues of forming and implementing the policy of product promotion in the company are elaborated, the directions of attracting changes to the dynamic fluctuations in the market activity of companies and creating mechanisms for successful implementation of the policy in the company are presented. Recommendations for the formation of a product promotion policy for the future, taking into account dynamic changes in the market environment, are developed. The results of the study in the area of branding are presented, the main levers of brand influence on the development of advertising companies are highlighted, attention is paid to integrated mechanisms for combining individual components into a single comprehensive advertising strategy. The author suggests ways of developing advertising management in terms of integration of traditional and digital formats of advertising management, i.e., the correct choice of the most effective for the purpose and audience of the company in the selected target market, focusing on interaction with the audience and providing interactive opportunities in advertising campaigns, as well as creating a constantly changing model of advertising management in accordance with market trends. The proposed measures should ensure the effectiveness of advertising management as an important component of the company's strategic management system to ensure an appropriate level of competitiveness when entering the market environment.
Keywords: advertising management; advertising campaign; strategic management; product promotion policy; branding; digital transformation